Eu e o outro na cidade : relações de autoria e audiência na pichação - Machado, Rodrigo de Oliveira (2014)
The presented study, requirement for the degree of Master in Psychology, is part of a basic understanding of social phenomenon through the historic matrix. Through this theoretical framework and dialogical contributions offered by linguistics, is meant the graffiti as communicative act in which the relationship of authorship and audience is concerning. Thus, the objective that guides this study is to understand the relations of authorship and audience present in the urban dialogue between the dyad taggersbystanders. The subject's approach succeeded in two complementary ways which constitute the body of this dissertation in two articles. The ethnographic approach went along and generated data concerning on the graffiti phenomenon during the five-year period (2009-2013) consisting of field diaries, photographic records, interviews with taggers, pedestrians and owners of commercial establishments in areas where the graffiti had spread in recent years. The collected material showed the personal relations between the taggers and the invisibility and visibility process that permeates their experiences in the city. The pursuit for ingroup and outgroup recognition were also important markers in the practitioners discourse, beyond the individualization of this act and its possible relation to such recognition. The relationship with the members of other practices such as graffiti proved to be unstable due to deviation of some graffiti artists what would be the beginning of the intervention of the street, ie, the transgression. When approaching from the perspective of self-dialogical, with the focus on interviews with taggers and passersby helped in understanding the positions of 'I' in both groups, when questioned about the relevant relation between authorship and audience to graffiti. The results manifest the difficulties of the two groups relate to otherness, presenting monologic discourse, strongly impregnated by consistently voiced positions in the media (passersby) and dicotomic (taggers). The difficulty of positioning in terms of otherness subsidizes the relations of distance between taggers and bystanders, giving negative aspects of the city experiences for both groups.